Inheritance of the mosaic and necroses reactions induced by bean severe mosaic comoviruses in Phaseolus vulgaris L - Morales, Francisco José; Singh, Shree P. (Springer, 1997)
The inheritance of the localized necrosis, apical necrosis, and mosaic reactions induced by bean severe mosaic comoviruses in common bean (Phaseolus vulgaris L.), was studied in crosses of Great Northern 123 × Pitouco, Great Northern 123 × Iguaçu and Pitouco X Iguaçu. Great Northern 123 reacts with mild mosaic, Iguaçu with localized necrosis, and Pitouco with apical necrosis to bean severe mosaic comoviruses. The analysis of the F1 and F2 generations indicated that localized necrosis was dominant over mild mosaic, and apical necrosis was dominant over the localized necrosis and the mild mosaic. An independently inherited single dominant gene controlled the expression of localized and apical necrosis in cultivars Iguaçu and Pitouco, respectively. The dominant gene for apical necrosis (Anv) found in Pitouco, was epistatic over the dominant gene (Lnv) conditioning localized necrosis in Iguaçu, as suggested by the F2 of Pitouco × Iguaçu, that yielded a ratio of 12 apical necrosis: 3 localized necrosis:1 mild mosaic. The genotypes of Pitouco, Iguaçu and Great Northern 123 are: Anv Anv lnv lnv, anv anv Lnv Lnv, and anv anv lnv lnv, respectively.